2007
DOI: 10.1258/135763307781644933
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study of acute plastic surgery trauma and burn referrals using telemedicine

Abstract: A store-and-forward telemedicine system was used to supplement normal telephone referrals to the plastic surgery unit at the Queen Victoria Hospital (QVH). During a 12-week prospective study, 11 units (8 hospitals and 3 minor injury units) with the telemedicine system and 10 units (8 hospitals and 2 minor injury units) without it regularly made referrals (at least 10) to the QVH. There were 389 referrals from the telemedicine-equipped units and 607 telephone referrals from the non-telemedicine units. The telem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 10 publications
(13 reference statements)
0
24
0
Order By: Relevance
“…6,7 Studies have shown that image-based consultation of remote experts is possible in several specialties like dermatology, plastic surgery, or burn care. [8][9][10][11][12] However, the evidence rests predominantly on studies where photographs were taken with a digital camera, and only a few were conducted using older models of mobile phones. [13][14][15][16][17] Against this background it appears necessary to take a closer look at the quality of pictures taken with smartphone cameras in order to determine the value of incorporating smartphones in medical practice.…”
mentioning
confidence: 99%
“…6,7 Studies have shown that image-based consultation of remote experts is possible in several specialties like dermatology, plastic surgery, or burn care. [8][9][10][11][12] However, the evidence rests predominantly on studies where photographs were taken with a digital camera, and only a few were conducted using older models of mobile phones. [13][14][15][16][17] Against this background it appears necessary to take a closer look at the quality of pictures taken with smartphone cameras in order to determine the value of incorporating smartphones in medical practice.…”
mentioning
confidence: 99%
“…Lower resolution systems (mobile phone screens) can result in discordance between face-to-face management and telemedicine assisted referrals (Hsieh et al 2004). We found no discordance for acute burn management (see figure 12) and a 3% discordance for hand injuries at 800 x 600 pixel resolution, see figure 11 (Wallace et al 2007). Compact digital cameras have now surpassed www.intechopen.com…”
Section: 21a Image Resolutionmentioning
confidence: 73%
“…The Telemedicine group had fewer attendances for clinical review, fewer referrals declined and increased use of day surgery. This significant difference was found in each of the three groups of closed, tidy and untidy injuries with the availability of telemedicine (Wallace et al 2007). Hand injury patients were triaged directly to Day Surgery with significantly greater accuracy, see figure 11.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations